2020
DOI: 10.1016/j.redox.2019.101400
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Cys residues in human thioredoxin-1 by p-benzoquinone causes inhibition of its catalytic activity and activation of the ASK1/p38-MAPK signalling pathway

Abstract: Quinones can modify biological molecules through both redox-cycling reactions that yield radicals (semiquinone, superoxide and hydroxyl) and via covalent adduction to nucleophiles (e.g. thiols and amines). Kinetic data indicate that Cys residues in GSH and proteins are major targets. In the studies reported here, the interactions of a prototypic quinone compound, p-benzoquinone (BQ), with the key redox protein, thioredoxin-1 (Trx1) were examined. BQ binds covalently with isolated Trx1 forming quinoprotein addu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
(76 reference statements)
2
9
0
Order By: Relevance
“…We also found that BQ led to the formation of non-reducible SETD2 protein cross-links/oligomers as previously observed for other enzymes inhibited by BQ (Fig. 2A and 2C) (Shu, Cheng, et al, 2020;Shu, Hägglund, et al, 2020). Interestingly, SETD2 has been shown to be inherently prone to protein crosslink/aggregation which can be detected by SDS-PAGE/western blot or immunofluorescence (Bhattacharya and Workman, 2020).…”
Section: Bq Forms Michael Adducts On Active Site Zinc-finger Cysteines and Impairs Irreversibly Setd2 Histone Methyltransferase Activitysupporting
confidence: 85%
See 3 more Smart Citations
“…We also found that BQ led to the formation of non-reducible SETD2 protein cross-links/oligomers as previously observed for other enzymes inhibited by BQ (Fig. 2A and 2C) (Shu, Cheng, et al, 2020;Shu, Hägglund, et al, 2020). Interestingly, SETD2 has been shown to be inherently prone to protein crosslink/aggregation which can be detected by SDS-PAGE/western blot or immunofluorescence (Bhattacharya and Workman, 2020).…”
Section: Bq Forms Michael Adducts On Active Site Zinc-finger Cysteines and Impairs Irreversibly Setd2 Histone Methyltransferase Activitysupporting
confidence: 85%
“…As shown in Fig. 4.A, exposure of transfected cells to BQ led to the formation of inactive SETD2 cross-links/oligomers as previously observed for other enzymes inhibited by BQ (Shu, Cheng, et al, 2020;Shu, Hägglund, et al, 2020). SETD2 is inherently prone to protein crosslink/aggregation and SETD2 aggregates/oligomers have been observed by immunofluorescence as puncta in cells (Bhattacharya and Workman, 2020).…”
Section: Impairment Of Setd2 Histone Methyltransferase Activity and Decreased H3k36me3 Levels In Cells Exposed To Bqsupporting
confidence: 74%
See 2 more Smart Citations
“…The substrates of Trx1 includes hydroperoxide [ 21 ], glutathione peroxidases that terminate lipids peroxidation cascade, and ribonucleotide reductase that is a key enzyme in DNA replication [ 17 ]. Moreover, the reduced form of Trx1 interacts with the N-terminal portion of apoptosis stimulating kinase 1 (ASK1) in vitro and in vivo , acting as a physiological inhibitor of ASK1, while the oxidation and release of Trx1 from ASK1 links cytotoxic stresses, such as TNF-α and H 2 O 2 , leading to activation of the p38 MAPK and SAPK/JNK stress response pathways [ 22 , 23 ]. Thus, Trx1 system is important for cell growth/survival as well as oxidative stress-induced signal transduction [ 24 ].…”
Section: Introductionmentioning
confidence: 99%